FAKTOR-FAKTOR YANG MEMPENGARUHI KONSUMSI MIE INSTAN PADA MAHASISWA - Islami Arza, Audina El; Yulastri, Asmar; Fridayati, Lucy (Journal of Home Economics and Tourism, 2017)
This study aimed to describe the factors that influence the consumption of instant noodles to students. This type of research is quantitative descriptive. Pulasi in this study is a student of Family Welfare Education, Faculty Of Tourism And Hospitality, State University of Padang class of 2011, 2012, 2013 and 2014, amounting to 160 people and a sample of 62 people. Data was collected using a questionnaire with multiple choice and Likert scale. Furthermore, the data were analyzed through descriptive analysis. The study concluded that the most influential factor in the consumption of instant noodles to students is the influence of peers. The factors that most influence on the low consumption of instant noodles is the attitude. Student knowledge about instant noodles quite good. The availability of instant noodles among students quite a lot and easily obtained. Intensity viewed media about instant noodles among students is quite frequent and relatively low student allowance.Keywords: Factors, consumption, instant noodles, student.